Thermo‐Photocatalysis: Environmental and Energy Applications. Issue 10 (4th April 2019) - Nair, Vaishakh; Muñoz‐Batista, Mario J.; Fernández‐García, Marcos; Luque, Rafael; Colmenares, Juan Carlos
Abstract: Catalysis is an integral part of a majority of chemical operations focused on the generation of value‐added chemicals or fuels. Similarly, the extensive use of fossil‐derived fuels and chemicals has led to deterioration of the environment. Catalysis currently plays a key role in mitigating such effects. Thermal catalysis and photocatalysis are two well‐known catalytic approaches that were applied in both energy and environmental fields. Thermo‐photocatalysis can be understood as a synergistic effect of the two catalytic processes with key importance in the use of solar energy as thermal and light source. This Review provides an update on relevant contributions about thermo‐photocatalytic systems for environmental and energy applications. The reported activity data are compared with the conventional photocatalytic approach and the base of the photothermal effect is analyzed. Some of the systems based on the positive aspects of thermo‐ and photocatalysis could be the answer to the energy and environmental crisis when taking into account the outstanding results with regard to chemical efficiency and energy saving. Abstract : In the heat of the light : Thermo‐photocatalysis is a new catalysis approach based on the synergistic mechanism of photo‐ and thermocatalysis that can operate under the emission of a solar spectrum (see image). The reaction mechanisms, reaction conditions involved in various thermo‐photocatalysis‐based reactions for different environmental and energy applications that have better efficiencies and desired characteristics compared to individual catalytic systems are reported.